PERLINDUNGAN HUKUM TERHADAP PELAKSANAAN PENGANGKATAN ANAK DITINJAU DARI HUKUM ISLAM DAN UNDANG-UNDANG NO 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Hamidansyah Putra Putra; Edy Ikhsan; Hasim Purba; Hasballah Thaib (USU LAW JOURNAL, 2015)
ABSTRACT Transparent and resolute regulation on adoption is highly needed, both in its regulation and in its protection. Today, the Government Regulation No. 54/2007 on the Implementation of Adoption, Law No. 23/2002 on Child Protection, and the Compilation of the Islamic Law regulate wajibah will for an adopted child. Discussion about adoption is usually related to adat (customary) law, the Islamic law, and western law in which people have different methods in different places in its implementation so that it is interesting to be analyzed. A research on child protection law about the implementation of adoption, viewed from the Islamic Law and Law No. 23/2002 on Child Protection, is a descriptive analysis which describes, explains, and analyzes laws theoretically and practically from the field. Keywords: Adopting a Child, Islamic Law, Child Protection